Evaluating Oil Palm Supply System Efficiency - Siti Noor Amira, Othman; Fazeeda, Mohamad; Razman, Mat Tahar; Ahmad Nazif, Noor Kamar (Penerbit Universiti Malaysia Pahang, 2016)
Malaysia is among the largest palm oil producer in the world. This paper contributes to measure value added of current facility in oil palm plantations in order to analyse the efficiency supply system operations of the plantations. Besides, the factors measures to be undertaken in the future in meeting to the efficiency of oil palm plantation’s supply system also been determined. The factors including the downtime due to the machines (mini tractors and trucks) breakdown or any mechanical problems were evaluated. Simulation is used in identify the key failure of increasing in delay time for fresh fruit bunches been transferred to the mill. Finding in this study show the highest value added in efficiency of oil palm plantation’s supply system is scenario III, which is by using mini tractors it will decrease the probability of waiting time when downtime occurs. As a result, it will increase level efficiency supply system operations of the oil palm plantations.